Analysis of Biodegradation of Bioplastics Made of Cassava Starch - Nanang Eko Wahyuningtiyas; Heru Suryanto (Journal of Mechanical Engineering Science and Technology (JMEST), 2017)
Environmental pollution due to plastic waste taking too long to decompose has become a global problem. There have been numerous solutions proposed, one of which is the use of bioplastics. The use of cassava starch as the main ingredient in the manufacture of bioplastics shows great potential, since Indonesia has a diverse range of starch-producing plants. The aim of the present study is to analyse the effect of glycerol on microbial degradation. This experimental research investigated the use of cassava flour mixed with glycerol plasticizer at various concentrations (0, 2, 2.5, 3%) in the synthesis of bioplastics. The aspects studied were biodegradability, moisture absorption (using ASTM D570), shelf life, and morphological properties (using a camera equipped with a macro lens) and SEM. This study revealed that complete degradation could be achieved on the 9th day. The addition of a large concentration of glycerol would accelerate the microbial degradation process, increase moisture, and extend the shelf life of bioplastics in a dry place.